Exploring the Interplay Between Thyroid Hormone Levels and Symptoms of Anxiety and Depression in Anorexia Nervosa - Lama Mattar; Anne‐Laure Delaunay; Sylvie Berthoz; Maeva Duquesnoy; Sylvain Iceta; Christophe Lalane; EVHAN group; Mouna Hanachi; Nathalie Godart (Brain and Behavior, 2025)
ABSTRACT Objective A strong association exists between anorexia nervosa (AN) and symptoms of depression, anxiety, and obsessive‐compulsive disorder (OCD). The levels of these psychiatric symptoms observed in AN may be influenced by different biological factors related to poor nutritional status and changes in thyroid hormone levels. Yet, few studies have investigated this relationship. The objective of this study is to examine the association between depression, anxiety, and obsessive‐compulsive (OC) symptoms and circulating thyroid hormones in a sample of undernourished patients with AN. Methods Two hundred and two patients with AN (DSM‐IV TR) were included in the study and were assessed upon admission for duration of illness, psychiatric treatments, sociodemographic data, and different psychopathological symptoms [depression (BDI), anxiety (HAD scale), obsessive‐compulsive (MOCI), social phobia (LSAS fear sub‐scale), and Eating Attitudes Test‐26 (EAT‐26)] using psychometric scales. Nutritional status was assessed with body mass index (BMI) and body composition using bioelectrical impedance. Upon patient admission, free‐T3 (fT3), free‐T4 (fT4), and TSH thyroid hormone plasma levels were collected, as well as albumin and transthyretin levels. Results Taking into consideration confounding factors, particularly the duration of AN evolution, thyroid hormone (fT3 and/or fT4) blood levels can partially explain the levels of depression and OCD symptoms of the doubt type and social phobia in undernourished AN patients. Conclusion A high prevalence of these symptoms among malnourished individuals requires investigation to differentiate between symptoms directly related to the biological effects of malnutrition and those indicative of a comorbid condition such as depression or anxiety.